Deficiency of Prebiotic Fiber and Insufficient Signaling Through Gut Metabolite-Sensing Receptors Leads to Cardiovascular Disease. Issue 17 (28th April 2020) - Kaye, David M.; Shihata, Waled A.; Jama, Hamdi A.; Tsyganov, Kirill; Ziemann, Mark; Kiriazis, Helen; Horlock, Duncan; Vijay, Amrita; Giam, Beverly; Vinh, Antony; Johnson, Chad; Fiedler, April; et al.
Abstract : Background: High blood pressure (BP) continues to be a major, poorly controlled but modifiable risk factor for cardiovascular death. Among key Western lifestyle factors, a diet poor in fiber is associated with prevalence of high BP. The impact of lack of prebiotic fiber and the associated mechanisms that lead to higher BP are unknown. Here we show that lack of prebiotic dietary fiber leads to the development of a hypertensinogenic gut microbiota, hypertension and its complications, and demonstrate a role for G-protein coupled-receptors (GPCRs) that sense gut metabolites. Methods: One hundred seventy-nine mice including C57BL/6J, gnotobiotic C57BL/6J, and knockout strains for GPR41, GPR43, GPR109A, and GPR43/109A were included. C57BL/6J mice were implanted with minipumps containing saline or a slow-pressor dose of angiotensin II (0.25 mg·kg -1 ·d -1 ). Mice were fed diets lacking prebiotic fiber with or without addition of gut metabolites called short-chain fatty acids ([SCFA)] produced during fermentation of prebiotic fiber in the large intestine), or high prebiotic fiber diets. Cardiac histology and function, BP, sodium and potassium excretion, gut microbiome, flow cytometry, catecholamines and methylation-wide changes were determined. Results: Lack of prebiotic fiber predisposed mice to hypertension in the presence of a mild hypertensive stimulus, with resultant pathological cardiac remodeling. Transfer of a hypertensinogenic microbiota to gnotobiotic mice recapitulated the prebiotic-deprived hypertensive phenotype, including cardiac manifestations. Reintroduction of SCFAs to fiber-depleted mice had protective effects on the development of hypertension, cardiac hypertrophy, and fibrosis. The cardioprotective effect of SCFAs were mediated via the cognate SCFA receptors GPR43/GPR109A, and modulated L-3, 4-dihydroxyphenylalanine levels and the abundance of T regulatory cells regulated by DNA methylation. Conclusions: The detrimental effects of low fiber Westernized diets may underlie hypertension, through deficient SCFA production and GPR43/109A signaling. Maintaining a healthy, SCFA-producing microbiota is important for cardiovascular health. Abstract : Supplemental Digital Content is available in the text.